THE EFFECT OF SCHOOL PRINCIPAL LEADERSHIP AND SCHOOL COMMITTEE’S ROLE ON THE IMPLEMENTATION OF SBM AT SD NEGERI GUNUNG TALANG SOLOK - Firman, Dalla; Asmendri; Aisyah, Devi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Principal leadership and the role of the school committee are factors influencing the implementation of SBM. The purpose of this paper is to describe (1) the effect of the principal's leadership (X1) on the implementation of SBM (Y), (2) the effect of the role of the school committee (X2) on Y, and (3) the effect of X1 and X2 simultaneously on Y at Gunung Talang State Elementary School in Solok. The research is ex post facto. The population of the research involves 284 state elementary school teachers in Gunung Talang Solok. The research sample is 74 people, which are selected using a stratified proportional random sampling technique. The research instrument is a questionnaire about principal leadership, the role of school committees, and the implementation of SBM through a Likert scale. Data were analyzed using SPSS version 20.0. Based on the research results, it is found that (1) there was a significant effect between X1 and Y with a significance value of 0.031 < 0.05, which means that Ha is accepted and H0 is rejected. In addition, (2) there is a significant effect between X2 and Y with a significance value of 0.017 < 0.05, which indicates that Ha is accepted and H0 is rejected. Subsequently, (3) there is a significant effect between X1 and X2 simultaneously on Y with a significance value of 0.000 < 0.05, which implies that Ha is accepted and H0 is rejected. Above all the findings, it can be concluded that the principal leadership and the school committee’s role are two factors that simultaneously influence the implementation of SBM at SD Negeri Gunung Talang Solok.